A reality-based guide to KMS diffusion - Xu, Jun; Quaddus, Mohammed (Emerald Group Publishing, 2005)
Purpose – To summarise the findings from research in adopting and diffusing knowledge management systems. Design/methodology/approach – The approach is a summary of the study findings and a discussion of these. Findings – The findings explain the adoption and diffusion of a KMS in an organization. These include: perceived usefulness has a positive relationship with an organization embarking on a KMS; people's decision to accept and use a KMS is directly determined by perceived user-friendliness and perceived voluntariness; and the KMS diffusion process takes place in six stages. Research limitations/implications – This study tested the entire research model. In the future, parts of the model could be extracted and investigated in detail. Practical implications – The results have significant implications for managerial practices, including the need for a KMS; the cost of a KMS; significant factors of KMS adoption and diffusion; end-user focus and involving people in the KMS; and organizational adjustment to embrace the KMS. Originality/value – The study develops and tests a comprehensive model of KMS adoption and diffusion.